Efficiency of training correction in canoeing based on post-exercise electrocardiogram changes - Makarova G.A.; Pogrebnoy A.I.; Karpov A.A.; Chernukha S.M. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the diagnostic potential of post-training electrocardiogram alterations in the context of current training regimen optimization for elite kayakers and canoeists. Methods and structure of the study. The electrocardiogram was taken from 28 male rowers aged 18 to 36 (3 Olympic champions, 7 international-level masters, 18 masters) and 18 female athletes aged 18 to 33 (2 Olympic champions, 4 international-level masters, 12 masters). The examination was conducted using the Valenta diagnostic system, with 12 standard leads, repeated at intervals of 3 to 12 days throughout the annual training cycle. A total of 1,360 measurements were taken. The following data were recorded: heart rate, the position of the heart’s electrical axis AQRS, the duration of the P, T, and QRS complexes, the PQ, QT, and QT corrected (Bazett) intervals, and the ST segment.; The Macruz index, the height of the R and T waves, and the ratio of the R to T wave heights in the fifth and sixth thoracic leads, the waveform, and the T-wave amplitude in all leads, the position of the PQ and ST segments relative to the isoelectric line, and the shape of the ST segment ascent were examined. Results and conclusions. It was discovered that the diagnostic value of an electrocardiogram diminishes significantly when it is taken only as part of a routine annual medical examination. To detect the slightest alterations that enable timely adjustment of training loads, it is essential to conduct at least one recording per week. Moreover, the new electrocardiogram must be meticulously compared with the previous one. It is also crucial to incorporate the ratio of K to N in the left chest leads and the measurement of the angle between the ascending and descending portions of the T-wave with its characteristic dome-like shape into the calculation of the recorded parameters. One of the initial abnormalities in the electrocardiogram of athletes may be the alignment of the S-T segment and the ascending portion of the T wave, as well as an increase in the absolute QT interval due to the S-T segment with a relatively stable corrected QT.